2011
DOI: 10.4161/auto.7.10.16660
|View full text |Cite
|
Sign up to set email alerts
|

ULK1 inhibits the kinase activity of mTORC1 and cell proliferation

Abstract: ULK1 (Unc51-like kinase, hATG1) is a Ser/Thr kinase that plays a key role in inducing autophagy in response to starvation. ULK1 is phosphorylated and negatively regulated by the mammalian target of rapamycin complex 1 (mTORC1). Previous studies have shown that ULK1 is not only a downstream effector of mTORC1 but also a negative regulator of mTORC1 signaling. ( 1-3) Here, we investigated how ULK1 regulates mTORC1 signaling, and found that ULK1 inhibits the kinase activity of mTORC1 and cell proliferation. Defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(122 citation statements)
references
References 44 publications
5
115
0
2
Order By: Relevance
“…Collectively, these multiple phosphorylations inhibit mTORC1 activity through hindrance of substrate docking to raptor [72]. These results are in line with the findings by Jung et al [73]. Collectively, the Ulk1-mediated phosphorylation of AMPK and raptor represent regulatory feedback loops and contribute to the positive and negative regulation of autophagy.…”
Section: The Ulk1-atg13-fip200 Protein Kinase Complex and Protein Phosupporting
confidence: 81%
See 1 more Smart Citation
“…Collectively, these multiple phosphorylations inhibit mTORC1 activity through hindrance of substrate docking to raptor [72]. These results are in line with the findings by Jung et al [73]. Collectively, the Ulk1-mediated phosphorylation of AMPK and raptor represent regulatory feedback loops and contribute to the positive and negative regulation of autophagy.…”
Section: The Ulk1-atg13-fip200 Protein Kinase Complex and Protein Phosupporting
confidence: 81%
“…Thus, we propose that Ulk1 is not only necessary for the induction of autophagy, but also is involved in its containment [68]. Finally, two reports describe the Ulk1-dependent phosphorylation of raptor [72,73]. The common theme here is that this phosphorylation leads to the inhibition of mTORC1 thus inducing autophagy.…”
Section: The Ulk1-atg13-fip200 Protein Kinase Complex and Protein Phomentioning
confidence: 97%
“…Thus, phosphorylation of RPTOR by ULK1 negatively regulates MTOR complex 1 23 and has also been proposed as a mechanism connecting ULK1 activity and cell proliferation. 24 Similarly, ULK1/2 phosphorylate all 3 subunits of AMPK and negatively regulate its activity, thereby terminating signaling that initiates autophagy. 25 If so, based on our results, it could be suggested that downregulation of ULK1 under starvation conditions could lead to more efficient activation of AMPK.…”
Section: Discussionmentioning
confidence: 99%
“…17 Upon activation, ULK1 suppresses cell growth and protein synthesis by inhibiting TORC1 while promoting autophagic degradation. 18,19 Reciprocal inhibition between ULK1 and TORC1 is suggested to be an interlocked feedback loop that serves as a Autophagy-related 1 (Atg1)/Unc-51-like protein kinases (ULKs) are evolutionarily conserved proteins that play critical physiological roles in controlling autophagy, cell growth and neurodevelopment. rB1-inducible coiled-coil 1 (rB1CC1), also known as PtK2/FAK family-interacting protein of 200 kda (FiP200) is a recently discovered binding partner of ULK1.…”
Section: Introductionmentioning
confidence: 99%